PENGARUH INVESTASI SWASTA DAN JUMLAH TENAGA KERJA TERSERAP TERHADAP PERTUMBUHAN EKONOMI KABUPATEN KETAPANG - B61110020, MURTADO (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The economic growth mirrors the economic activities in a country or government. It can be of positive or negative values. If in one economic period, the economy experiences positive growth, it means that there is an increase in the economic activities. On the contrary, if it shows negative growth, there is a decrease in the economic activities. During the period of 1996-2010, the economic growth of Ketapang is very fluctuative. . The regional economic growth can be influenced by various factors, among other things the foreign investment, the domestic investment, and the number of workforce employed. This reseach is conducted to know the influences of the foreign investment, the domestic invenstment , and the number of the workforces employed on the economic growth. The Data collected in this research are based on the secondary data. In this research, the method used is OLS (Ordinary Least Square). The findings of this research have shown that the foreign investment, the domestic investment, and the number of the workforces employed have the insignificant influence on the economic growth partially or simulteneously. . Key words : Foreign Investment , Domestic investment , the absorption of the workforce, Economic growth .